A preliminary evaluation of in vivo response to a filament‐wound macroporous collagen midurethral sling in an ovine model. Issue 12 (2nd July 2022) - Khalifa, Ahmad O.; Isali, Ilaha; Celik, Hakan; Mastran, Michael; McClellan, Phillip; Gillespie, Callan; Shankar, Subba; MacLennan, Gregory T.; Anderson, James M.; Schumacher, Fredrick R.; Akkus, Ozan; Hijaz, Adonis K.
Abstract: Stress urinary incontinence (SUI) impacts 1/3 of women over age 50. Negative publicity around PP meshes used in pelvic prolapse repair drives the need for identifying alternative biomaterials for SUI repair. Our study evaluated in vivo response to collagen sling implanted in an ovine model. Electrocompacted collagen threads were filament wound as slings and crosslinked in genipin. Collagen slings were implanted suburethrally mimicking the transvaginal tape technique. Main study groups were: Collagen sling ( n = 3, 6 months) and PP sling ( n = 3, 6 months). Collagen sling was also tested at 3‐weeks ( n = 1) to observe early‐stage tissue response and 1‐year ( n = 2) to assess biomaterial longevity in a preliminary capacity. Collagen slings healed to a fibrous ligament texture at 6 months and maintained such texture to 1 year. Histological scoring indicated biocompatible responses to collagen slings with no adverse events. All study groups exhibited complete tissue ingrowth and interstitial de novo collagen deposition at all time points. Collagen threads induced orderly de novo collagen deposition that was aligned along long axes of threads. Tissue infiltrated collagen slings that were explanted at 6 and 12 months presented similar structural strength with native tissues such as vagina and fascia, and PP (Lynx) slings ( p > .05). With the limitation of low number of animals per time point in hindsight, this preliminary study justifies evaluation of collagen slings in a larger sample size of animals, particularly to assess persistence of ligamentous tissue response over longer durations than 1‐year.